2014
DOI: 10.1159/000363036
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Loop of Autocrine BDNF from Microglia Causes Prolonged Microglia Activation

Abstract: Background/Aims: Microglia, which represent the immune cells of the central nervous system (CNS), have long been a subject of study in CNS disease research. Substantial evidence indicates that microglial activation functions as a strong neuro-inflammatory response in neuropathic pain, promoting the release of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α. In addition, activated microglia release brain-derived neurotrophic factor (BDNF), which acts as a powerful cytokine. In this study, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 27 publications
(31 reference statements)
1
46
0
Order By: Relevance
“…Our in vivo study showed that S100A8 resulted in microglial activation following the occurrence and development of surgery-induced neuroinflammation and cognitive dysfunction [36]. Activated microglia can release BDNF, which causes prolonged microglial activation [37]. Therefore, the inhibition of microglial activation and subsequent neuroinflammation may offer prospective clinical therapeutic benefits for neuroinflammation-related neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 84%
“…Our in vivo study showed that S100A8 resulted in microglial activation following the occurrence and development of surgery-induced neuroinflammation and cognitive dysfunction [36]. Activated microglia can release BDNF, which causes prolonged microglial activation [37]. Therefore, the inhibition of microglial activation and subsequent neuroinflammation may offer prospective clinical therapeutic benefits for neuroinflammation-related neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 84%
“…In vivo activation of TrkB by DHF administration has also been demonstrated in a number of experimental systems (Tzeng et al 2013, Zhang et al 2014). With 5 mg/kg/day DHF administration for 10 days (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…This imbalance between excitatory and inhibitory neurotransmission has the potential to cause side effects, especially in DHF-treated, sham-irradiated controls. Finally, TrkB is expressed in various neuronal and glial populations and its activation has the potential to affect excitatory and inhibitory circuits, as well as neuroinflammation, in different brain regions (Huang and Reichardt 2003, Zhang et al 2003, Zhang et al 2014). A clear understanding of the effects of DHF on different cell populations will be crucial to designing effective treatments for various neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF release to the spinal cord has been extensively studied where BDNF acts on spinal neurons facilitates spinal cord plasticity and long-term potentiation (LTP)-like activities, and is believed to contribute to spinal “central sensitization” (Tonra et al, 1998, Lever et al, 2001, Luo et al, 2001, Ng et al, 2007, Ha et al, 2008). BDNF is also able to act on microglia and facilitates tumor necrosis factor-α (TNF-α) release (Zhang et al, 2014), and TNF-α-potentiated N-methyl-D-aspartate (NMDA) receptor activation (Xu et al, 2010). BDNF release along the distal (peripheral) axonal branch has not been characterized.…”
Section: Discussionmentioning
confidence: 99%